(untitled) (UNED Research Journal, 2019)
Democracy is measured by the degree of citizen participation in decision-making processes, not only those that are procedural, but also those that require people own action. Despite the importance of participatory processes, as well as the dedication of time and economic resources provided by States to the formulation of public policy related to addressing climate change, in many Latin American populations, they perceive that the processes are not suitable, sufficient or efficient. While it is true that, from the Government, these spaces should be promoted and actions taken to strengthen citizen skills, as well as institutional capacities and the regulatory body to achieve participatory processes of weight, as citizenship we must question whether we are really demanding these spaces of the best way and in the cases where they exist, if we are making a correct, profitable and strategic use. The information, the issuance of assertive criteria, and an active intervention, are levels of participation that ideally should always be present, strengthening both the structures and the actions for governance, in search of the common good. The most evolved forms of conflict resolution should be clear that democracy is not equal to the unanimity, and that these processes rather seek common ground in pluralism. A weakening of participatory processes can cause a weakening of democracy, poor management of public goods and services, and therefore the privatization of the State. This implies that as citizens we must learn to inform ourselves, to be clear about our interests, to dialogue and negotiate in search of agreements, and to consider, therefore, the diversity of opinions in the process.